The Effect of Trust on M-Banking in Online Transactions on E-Customer Loyalty: A Theoretical Approach - Jonathan Frederico; Endi Sarwoko; Romauli Nainggolan (Green Publisher Indonesia, 2025)
The intensifying competition in the digital banking sector, accelerated by shifts in consumer behavior, underscores the critical role of customer trust and satisfaction in fostering loyalty. This study investigates the effect of trust in mobile banking on e-customer loyalty, with re-use intention as a mediating variable, utilizing the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. This research employs a quantitative descriptive approach to examine whether customer satisfaction and trust have a noteworthy impact on loyalty when using mobile banking, with re-use intention acting as a mediating variable. The study’s sampling strategy is snowball sampling, which is conducted randomly. Questionnaire data are used as the method to gather information for this investigation. Beginning with data collection, data reduction, data display, and conclusion explanation, the data analysis procedures are implemented in multiple phases. The findings, analyzed using SPSS, demonstrate that both customer trust and satisfaction significantly and positively influence loyalty. Furthermore, trust is found to significantly affect re-use intention, which, in turn, acts as a strong and significant mediator between trust and loyalty. The research model explains 95.4% of the variance in loyalty. The study implies that banks should prioritize building robust security and trustworthiness while enhancing user satisfaction to strengthen re-use intention and, ultimately, cultivate long-term customer loyalty in the competitive digital banking landscape.